Athlete monitoring - the foundation for informed decision-making - Karlsson, O. (Journal of Biathlon Coaching, 2024)
Athlete monitoring is considered essential for optimizing training and protecting the health of athletes. It involves the collection of a wide range of variables related to both training and competition, as well as non-training-related variables such as recovery, health, travel, and general well-being. The overarching goal of athlete monitoring is to facilitate informed decisions that can improve the training process and ultimately enhance performance. While a plethora of methods are available, choosing the ones appropriate for your specific context is key to succeeding with athlete monitoring over time.